SHIFTING AND CONTESTATION OF RELIGIOUS AUTHORITIES IN ACEH: FROM ABU, TENGKU, WALED TO—USTAZ - Saputra, Eko; Fadhli, Fadhli (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2020)
This article discusses the 'shift' and ‘contestation' of religious authority in Aceh. The emergence of the ustadz Salafi through new media has fragmentation traditional religious authorities and at the same time has been created religious contestation in Aceh. Interestingly, the contestation occurred among between fellow traditional religious authorities, not but between new religious authority and traditional religious authority (or vice versa). This study used field research collaborated with the netnography (online) of